Pengaruh Mekanisme Good Corporate Governance, Dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan (Studi Kasus pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012) - Wahyudi Saputra; Desmiyawati '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to examine the effect of institutional ownership, managerial ownership, audit committees, auditors the quality and size of the company for the integrity of the financial statements. The population in this study is a manufacturing company in Indonesia Stock Exchange (IDX). The period of observation was in 2012. According to data from the Indonesia Stock Exchange there are 164 manufacturing company during the period of observation. The technique used in the determination of the sample is purposive sampling method, where the sample set by using certain criteria. Based on these criteria there are 124 (one hundred and twenty-four) companies. Analysis of data using multiple regression methods. The results stated that institutional ownership has no significant effect on the integrity of the financial statements. Managerial ownership has no significant effect on the integrity of the financial statements. Reputation KAP has a significant effect on the integrity of the financial statements. Firm size has a significant effect on the integrity of the financial statements.Keywords: Institutional Ownership, Managerial Ownership, Firm Reputation, Corporate Size and Integrity Financial Statements.